(untitled) (Boston, MA., 2006)
Political, technological, market, cost and competitive changes have driven many businesses to expand operations globally – creating an explosion in the growth rate of international businesses. Firms operating across borders must also deal with the following forces in foreign and domestic environments: competitive, distributive, economic, socioeconomic,...The relationship of the forces in foreign and domestic environments forms the basis of Ball & McCulloch’s International Business model
Keywords: International business enterprises,International business enterprises.,International economic relations; Management